GESTÃO SOCIAL E CIDADANIA: O PORTAL GSC - Padilha, Milena Roberta Basso; Possebon, Jéssica; Prediger, Reneo Pedro; Mueller, Airton Adelar; Allebrandt, Sérgio Luis; Krüger, Roseli Fistarol (Salão do Conhecimento, 2018)
Projeto de extensão gestão social e cidadania